Microscopic Mechanism of the Interaction in the Adsorption of Caramel Pigments onto Rosin-Based Decolorizing Resin for Sugar - WEI Yanhong, WANG Jiaxin, JIAO Li, LIAO Chunyu, LEI Fuhou, LI Wen (Shipin Kexue)
Decolorization of remelt syrup is the most critical step in sugar refining. Currently, benzene-based anion-adsorption resins are commonly used in remelt syrup decolorization, but their slow release of monomers may endanger food safety. In this study, a green and environmentally friendly rosin-derived macroporous anion-adsorbing resin was synthesized and used to efficiently capture the caramels in remelt syrup. The results showed that the equilibrium adsorption capacity of the resin for caramels was 86 mg/g, and the corresponding decolorization efficiency was as high as 90%. Following five cycles of repeated use, the decolorization efficiency decreased by only 5%, indicating excellent reusability. The focus was on the multidimensional visualization of the micro-mechanism of the interaction in the adsorption of caramels by the rosin-based resin at the molecular, atomic, and electronic levels on the basis of quantum chemical theoretical calculations (including electrostatic potential, electrostatic potential interaction, average local ionization energy, frontier molecular orbitals, independent gradient model, and Hirshfeld surface analyses). The results indicated that the adsorption occurred with positive-negative potential neutralization and interpenetration. The interaction mechanism was primarily mediated by the electrophilic reaction between carboxylate and protonated tertiary amine groups, followed by weak hydrogen bonding, with the resin acting as a hydrogen bond donor. The combined use of multiple quantum chemical theory calculations to visualize the micro-mechanism of the adsorption interaction can provide novel insights into exploring the adsorption behavior and mechanism at a deeper level, which has a theoretical contribution and practical value.